Editorial - Almouloud, Saddo Ag; Lucia Manrique, Ana (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2021)
Editorial of the volume 23-2-2021 in Portuguese, English, Spanish and French